2007
DOI: 10.1007/s00586-007-0519-3
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of post-operative pain patterns following total lumbar disc replacement: results from fluoroscopically guided spine infiltrations

Abstract: Although a variety of biomechanical laboratory investigations and radiological studies have highlighted the potential problems associated with total lumbar disc replacement (TDR), no previous study has performed a systematic clinical failure analysis. The aim of this study was to identify the post-operative pain sources, establish the incidence of post-operative pain patterns and investigate the effect on post-operative outcome with the help of fluoroscopically guided spine infiltrations in patients from an on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 72 publications
(116 reference statements)
2
27
0
Order By: Relevance
“…Similar to the results of Siepe et al [22,23], the patients with clinical failure reported pain during the early postoperative stage without apparent FJD at this time. The early and final clinical scores correlated with each other.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Similar to the results of Siepe et al [22,23], the patients with clinical failure reported pain during the early postoperative stage without apparent FJD at this time. The early and final clinical scores correlated with each other.…”
Section: Discussionsupporting
confidence: 88%
“…Our probabilistic FEM study identified that sagittal misalignment can cause both, increased facet joint capsule tensile forces in the case of iatrogenic posterior translation and increased compressive forces when iatrogenically shifting the superior vertebra anteriorly [27]. Although both situations would theoretically explain the development of FJD in patients with TDR [19][20][21][22][23], we have proven that especially a posterior translation of the superior vertebra leads to clinical failure. As discussed, posterior translation leads to higher capsule tensile or shear forces.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…This hypothesis seems to be partially proven when looking at the results of Punt et al [14], who stated facet joint arthrosis as possible cause of failure after TDR. Recently, Siepe et al [17] also reported of a substantial percentage of patients (33.1%) with significant pain after TDR. In 12.6% of their patients, the lumbar facet joints were diagnosed as the source of pain, mostly located at the index level.…”
Section: Discussionmentioning
confidence: 92%
“…If indeed the pregnancy-related pelvic pain is from the sacra-iliac joint, it is curious that the clinical features of so-called sacroiliac pain after fusion or indeed after lumbar disc replacement are so different. Siepe in 2008 [47] investigated 175 patients with back ache after disc replacement, by using local anaesthetic injections, and found that in 12 % the pain was from the sacroiliac joint. However, the pattern described was quite unlike the pelvic pain of pregnancy.…”
Section: R C Mulholland (And)mentioning
confidence: 99%